Mapau Na Maloppo Batu (Konsep Adaptasi Kultural dan Identitas Tionghoa Muslim di Bulukumba Sulawesi Selatan) - Muslim, Abu; Nensia, Nensia; Rahmatullah, Rahmatullah; Suriati, Suriati; Amin, Saifuddin Amin (Center for Research and Development of Religious Literature and Heritage, 2023)
This article aims to explore the concept of cultural adaptation and the identity of Chinese Muslims in Bulukumba, South Sulawesi. Through a life story approach, this study employed observation on the daily life of key participants, in-depth interviews, and documentation. The results of the study showed that Chinese Muslims in Bulukumba experienced culture-sensitive adaptation process where their individual backgrounds and life experiences interacted with Islamic teachings and Bugis-Makassar-Konjo culture through assimilation. The cultural adaptation was visible in various aspects of life, such as religious practices, traditions, language, food, and social behaviour. In addition, the Chinese Muslim identity in Bulukumba resulted from a fusion of Chinese cultures and non-Chinese Muslims. This identity was reflected in language, appearance, and religious practices. Through life story studies, this research provided a comprehensive picture of how individuals experienced cultural adaptation and developed identity as Chinese Muslims in Bulukumba, known as Mapau na maloppo batu, as a manifestation of honesty and sincerity to be kind to fellow human beings.